2007
DOI: 10.4102/curationis.v30i2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and family members’ knowledge and views regarding diabetes mellitus and its treatment

Abstract: Diabetes mellitus affects millions of people worldwide and its related complications continue to be of great concern. The outcome of diabetes depends mainly on the patient’s self-management. Health care professionals therefore have a major responsibility to assist patients to acquire the essential knowledge, skills and attitudes towards self-management. A quantitative survey was conducted to identify diabetic patients and family members' knowledge and views about diabetes and its treatment regimen. A convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 8 publications
5
27
2
Order By: Relevance
“…Men focused on socio-economic factors, particularly the affordability of drugs, sexual function and lifestyle, while women valued well-being, support in daily life and household activities and had a higher risk awareness of DM. The indication of limited knowledge was in accordance with findings shown in previous investigations focusing on knowledge of DM in people in Cameroon and South Africa [12,13], and little understanding of the nature of DM, with reporting of a spectrum of different causes of DM in an investigation of the impact of the disease in Nigerians with DM [14], while in Ghanaians diagnosed with DM a blend of commonsense, scientized, and religious knowledge modalities that merged with biomedical goals, specifically drug and diet management [15]. …”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Men focused on socio-economic factors, particularly the affordability of drugs, sexual function and lifestyle, while women valued well-being, support in daily life and household activities and had a higher risk awareness of DM. The indication of limited knowledge was in accordance with findings shown in previous investigations focusing on knowledge of DM in people in Cameroon and South Africa [12,13], and little understanding of the nature of DM, with reporting of a spectrum of different causes of DM in an investigation of the impact of the disease in Nigerians with DM [14], while in Ghanaians diagnosed with DM a blend of commonsense, scientized, and religious knowledge modalities that merged with biomedical goals, specifically drug and diet management [15]. …”
Section: Introductionsupporting
confidence: 92%
“…Thus, it is important is to organize health care in a way that elicits individual beliefs about health and illness in persons with DM and then supports and provides the individual with appropriate information to strengthen the patient's self-care capability to become an active participant and partner in diabetes care [13]. In a country and life situation with a highly strained economic situation, as for example in Zimbabwe today [20] and in many other developing countries, health care needs to switch from predominantly focusing on disease control and compliance with medication to a holistic attitude starting from an individual perspective but also considering social determinants of health [26,30] to promote health and prevent DM and complications related to DM [26] in order to decrease the burden of the disease in light of the overarching pandemic of DM [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…There is opportunity for improvement, as only 32% reported that their family members were involved in the diabetes education consultation. This is supported by various studies showing that involvement of the family in patient care was strongly associated with diet, physical activity, and medication compliance [28,[31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 49%
“…It is a significant public health concern because of the demands it places on health care services and individuals [2, 3]. The pandemic mainly affects developing countries, particularly in Africa [3, 4] and the predicted number of affected people will double to 438 million in 2030 [1].…”
Section: Introductionmentioning
confidence: 99%